Liquidity and profitability of oil and gas industry in Malaysia - Ismail N.; Mohamad N.M.; Ramli A.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper aims to reveal the impact of liquidity towards profitability of oil and gas industry in Malaysia. The analysis is based on a sample of 25 oil and gas companies that are listed in Bursa Malaysia for the period of 2012 to 2018. Regression analysis was used to test the impact and the trend of financial position after and before decreasing oil price. The result shows that there is a significant impact of only quick ratio on Return on Assets (ROA), Return on Equity (ROE) and Return on Invested Capital (ROIC). While for the cash conversion cycle, the result shows that there is a negatively and significant on ROA, ROE and ROIC. However, for the current ratio, it shows the result as insignificantly with the three dependent variables; ROA, ROE and ROIC. The main results of the paper demonstrate that each ratio (variable) has a significant impact on the financial positions of oil and gas industry with differing amounts and that along with the liquidity ratios in the first place. In addition, this paper shows the results that after the crisis of dropped in oil price, its affected to the oil and gas industry in Malaysia. BEIESP.